Avaliação da segurança de trabalho em biorrefinarias de cana-de-açúcar - Maeda, Kelly (Universidade Federal de São Carlos, 2021)
The growing increase in cases of work accidents has been registered, also resulting in an increase in deaths in Brazil. This implies the need for specific risk assessment in order to define mitigation measures that can minimize the impact of hazards on workers' health. Through this study, it will be possible to assess the risks to which the alcohol, sugar and biogas production industries are subjected, their scientific and technological advances in terms of safety and then propose an ideal biorefinery prototype in terms of industrial safety through recommendation of a series of preventive measures. For this, surveys of accidents registered in these sectors were carried out, both in Brazil and around the world, through a literature review that included 22 publications, including articles, TCCs, dissertations and theses, in addition to safety manuals. There was an absence of Brazilian studies related to safety in biogas production, while studies on the sugar and alcohol industry were concentrated in the state of São Paulo. Regarding the main hazards found in the production of biogas and in sugar and ethanol plants, there are explosions and problems related to high temperatures, respectively. To avoid them, pressure and temperature control valves, gas leak monitoring systems and, mainly, management focused on the maintenance and training of workers are needed. For the creation of integrated and safe plants, a series of prevention measures that can suit both are necessary, indicating that good industrial safety practices apply in both cases.
Scientific and technological advances in process safety in the sugar-alcohol and biorefineries sector
Scientific and technological advances in process safety in the sugar-alcohol and biorefineries sector
Keywords: Acidente de trabalho, Biogás, Cana-de-açúcar, Incêndio, Riscos.; Acidente de trabalho, Biogás, Cana-de-açúcar, Incêndio, Riscos.; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA